2021
DOI: 10.1186/s40104-021-00599-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between the rumen microbiota and feed efficiency in Nellore steers

Abstract: Background Ruminants rely upon a complex community of microbes in their rumen to convert host-indigestible feed into nutrients. However, little is known about the association between the rumen microbiota and feed efficiency traits in Nellore (Bos indicus) cattle, a breed of major economic importance to the global beef market. Here, we compare the composition of the bacterial, archaeal and fungal communities in the rumen of Nellore steers with high and low feed efficiency (FE) phenotypes, as mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 63 publications
6
32
0
Order By: Relevance
“…This might be explained by previous observations that higher intestinal microbial diversity and richness result in a more stable and functionally complete intestinal ecosystem, which means that animals have better adaptability and higher productivity ( Firkins and Yu, 2015 ; Huws et al, 2018 ). However, we found no differences in diversity and richness of duodenum and jejunum with different RFI phenotypes, previous studies were similar to our result ( Li and Guan, 2017 ; Perea et al, 2017 ; Paz et al, 2018 ; Freetly et al, 2020 ; Lopes et al, 2021 ). This implies that efficiency status does not depend on a large-scale restructuring of the entire microbial community, but might be dependent on differences in a few key taxa ( Perea et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This might be explained by previous observations that higher intestinal microbial diversity and richness result in a more stable and functionally complete intestinal ecosystem, which means that animals have better adaptability and higher productivity ( Firkins and Yu, 2015 ; Huws et al, 2018 ). However, we found no differences in diversity and richness of duodenum and jejunum with different RFI phenotypes, previous studies were similar to our result ( Li and Guan, 2017 ; Perea et al, 2017 ; Paz et al, 2018 ; Freetly et al, 2020 ; Lopes et al, 2021 ). This implies that efficiency status does not depend on a large-scale restructuring of the entire microbial community, but might be dependent on differences in a few key taxa ( Perea et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
“…This implies that efficiency status does not depend on a large-scale restructuring of the entire microbial community, but might be dependent on differences in a few key taxa ( Perea et al, 2017 ). Additionally, some studies also observed no differences in rumen microbial diversity of cattle with different RFI phenotypes ( Paz et al, 2018 ; Clemmons et al, 2019 ; Lopes et al, 2021 ). These results might indicate that the diversity of the microbial community is not necessarily related to the RFI phenotype of animals.…”
Section: Discussionmentioning
confidence: 99%
“…Lachnospiraceae_XPB1014_Group was reported to participate in the degradation of fiber ( 49 ). Previous research reported that the family Lachnospiraceae , including Lachnospiraceae_ XPB1014_ group , tended to have greater relative abundance in Nellore steers with low nitrogen retention and in low-feed-efficiency beef cattle ( 50 , 51 ), which may be explained by the tryptophan metabolism and degradations of valine, leucine, and isoleucine ( 52 ). Fowler et al ( 8 ) investigated that HMBi would sustain ruminally available Met and potentially increase the efficiency of microbial protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The ASVs associated with L-RFI (e cient animals) both rumen and stool environments were taxonomically classi ed as belonging to the Rikenellaceae (gut group RC9). OTUs classi ed as belonging to this gut group were recently linked to low RFI in the rumen of Nelore steers, and to low FCR in the stool of pigs (Quan et al, 2018;Lopes et al, 2021), which, altogether, indicates a role of this speci c taxon on this phenotype. The Rikenellaceae (gut group RC9), as other members of the Rikenellaceae family, can produce different SCFAs, such as propionate, acetate and succinate, some with anti-in ammatory properties (Tedelind et al, 2007;Parada Venegas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome structure of the Nelore Brazilian beef cattle has gained the attention of the scienti c community in the past years, being subject of different studies (de Oliveira et al, 2013;Lopes et al, 2021), including a previous study by our research group (Andrade et al, 2020) . In this study, we investigated the microbiome pro les of two segments of 26 Nelore bulls' gastro-intestinal tract (GIT), and showed that a signi cant part of the stool archaeal population co-occurred with the rumen archaeal population, suggesting the use of stool as a proxy for the rumen archaeal population.…”
mentioning
confidence: 99%